Unimas Vehicles On Road Monitoring And Recognition (Iot System) - Nur Farah Hanis, Ahmad Masdil Fazli (Universiti Malaysia Sarawak (UNIMAS), 2023)
UNIMAS Vehicles On Road Monitoring And Recognition (IOT System) is is the system to take down all the vehicles speeding issues on UNIMAS. Students and staff are not excluded from facing this system. The report provides a system in UNIMAS that uses mobile devices via Raspberry Pi to detect passing cars and recognize those that violate the speed limit. Vehicle monitoring activities are carried out by assessing the intensity of capture data from Canny Edge Detector Algorithm and IR sensors received for summons. This method is appropriate for crowd sourcing applications that aim to reduce travel time, congestion, and pollution. During the experimental assessment, the advantages of the introduced technique were proven. The experimental assessment results will confirm that the recommended approach is successful. Extensive tests were carried out to evaluate various categorization methodologies and data aggregation methods.